Pengaruh Disiplin dan Motivasi terhadap Kinerja Karyawan pada SMK SASMITA JAYA I Pamulang - Sukapti, Sri (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2019)
The purpose of this research is to find out whether there is a positive and significant effect of discipline on employee performance, to find out whether there is a positive and significant effect on motivation on employee performance and to find out whether there is a positive and significant influence of discipline and motivation on employee performance simultaneously. This research was conducted to employees of SMK SASMITA JAYA I PAMULANG. This research uses quantitative descriptive methods with survey techniques. The data collection instrument used was a closed questionnaire with a Likert scale with a population of 110 employees, with a sample of respondents as many as 110 employees in SMK SASMITA JAYA I PAMULANG. Data were analyzed using statistical methods with SPSS version 23 for windows. The results of this study indicate that: (1) The results of the disciplinary hypothesis test show a t value of 9.044 which is then compared with t table of 1.982, which means that the hypothesis in this study rejects Ho and accepts Ha. Thus it can be concluded that the H1 hypothesis